Design of 2'-O-methyl RNA and DNA double-stranded oligonucleotides: naturally-occurring nucleotide components with strong RNA interference gene expression inhibitory activity. (20th February 2020) - Koizumi, Makoto; Hirota, Yasuhide; Nakayama, Makiko; Tamura, Masakazu; Obuchi, Wataru; Kurimoto, Akiko; Tsuchida, Hiroshi; Maeda, Hiroaki
Abstract: Double-stranded RNAs consisting of 21-nucleotide passenger and guide strands, known as small interfering RNAs (siRNAs), can be used for the identification of gene functions and the regulation of genes involved in disease for therapeutics. The difficulty with unmodified siRNAs lies in the chemical synthesis of RNA, its degradation by RNase, the immune response derived from natural RNA, and the off-target effects mediated by the passenger strand. In this study, asymmetrical 18 base-paired double-strand oligonucleotides comprised of alternately combined DNAs and 2′- O -methyl RNAs, denoted as MED-siRNA, were evaluated. These modified oligonucleotides showed high RNase resistance, a reduced immune response, a highly efficient cleavage of target mRNA with binding to Argonaute 2 (Ago2) via RNA interference, and the subsequent reduction of target protein expression. These findings suggest the possibility of alternatives to unmodified siRNAs with potential use in therapeutics.